Essential oils and phytogenic feed additives in ruminant diet: chemistry, ruminal microbiota and fermentation, feed utilization and productive performance - Kholif, Ahmed E.; Olafadehan, Olurotimi A. (Phytochemistry reviews, 2021)
A systematic approach was used to review, elucidate and summarize the importance of phytochemicals and essential oils (EO) as substitutes for chemical feed additives in ruminant feeding. Using PRISMA statement for defined search strategy, screening, selection and obtaining reliable conclusions, only articles that met the predefined selection criteria were used for the review. Phytochemicals feed additives (PFA) contain EO and a lot of other plant secondary metabolites (PSM). Essential oils are volatile aromatic compounds in most cases, and they compose of terpenoids and phenylpropanoids, which have antimicrobial properties. They have been the subject of persistent consideration of animal nutritionists who have been evaluating their use as feed additives to enhance ruminal fermentation and feed utilization efficiency. As alternatives to non-nutritive chemical and antibiotic feed additives, many phytochemicals (i.e. PSM), from a broad spectrum of herbs and spices, have been used to modify ruminal fermentation characteristics, inhibit ruminal methanogenesis and enhance livestock performance. The main limitations of PFA are defining the optimal doses that enhance animal performance and the adaptation of ruminal microflora to their presence in diets, resulting in inconsistent and inconclusive results. Many factors affecting the effective dose of phytochemicals include the chemical structures of phytochemical supplements/additives, the animal diet and animal physiological status. This review illustrates the possibility of using PFA on ruminal microbiota and their adaptation to phytochemicals, ruminal fermentation and animal performance.